Pengaruh Pengembangan Karir Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Grindak Artha Prima Jakarta Selatan - Tarissa Dwi Andriani; Vega Anismadiyah (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of career development and work motivation on employee performance at PT. Grindak Artha Prima South Jakarta. The method used is quantitative with an associative approach. The sampling technique uses saturated sampling and a sample of 60 respondents is obtained. Data analysis uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The results of this study are that career development does not have a significant effect on employee performance with a determination coefficient value of 62.3% and the hypothesis test obtained t count> t table or (1.993> 2.002). work motivation has a significant effect on employee performance with a determination coefficient value of 67.3% and the hypothesis test obtained t count> t table or (3.663> 2.002). career development and work motivation simultaneously have a significant effect on employee performance with a regression equation Y = 9.236 + 0.462X1 + 0.505X2. The coefficient of determination value is 69.4% while the remaining 51.8% is influenced by other factors. Hypothesis obtained calculated F value > F table or (64.777 > 2.770).